Utilization of Pregnancy Related Care Among Female Tea Garden Workers: Utilization of pregnancy related care (Journal of Preventive and Social Medicine, 2020)
Introduction: Utilization of pregnancy related care have crucial role in the improvement of reproductive health. Though Bangladesh has taking efforts by introducing various women-oriented development programs to limit the maternal mortality and morbidity, these services are poorly available to the deprived group. They are still struggling with their low utilization of pregnancy care.Objective: The study is aimed to find out the state of utilization of pregnancy related care among female tea garden workers.Materials and Methods: A cross sectional study was carried out from January to December 2017 among 326 purposively selected female workers residing in tea gardens of Sylhet having a baby of 42 days to one year. A pretested semi-structured questionnaire was used for face to face interview to document the information about their antennal care, intranatal care and postnatal care utilization. Data were analyzed by SPSS software.Results: The utilization of antenatal care was 52%, institutional delivery was 12.3%, had skilled attendant at birth 18.1% and received postnatal care 16.6% among the study population. Respondents antenatal care seeking was associated with their age (ρ=0.003), religion (ρ=0.000), literacy level of self (ρ=0.000) and husband (ρ=0.002) and their monthly family income (ρ=0.014). Place of last delivery of respondents was associated with their age (ρ=0.001). Literacy level of respondents (ρ=0.023) and that of their husbands (ρ=0.019) and their monthly family income ((ρ=0.015) was also associated with respondent’s birth attendant in their last delivery. In this study respondents postnatal care seeking is associated with their husband’s literacy level (ρ=0.010) but not associated with their age group (ρ=0.420), religion (ρ=0.067), their own educational status (ρ=0.370), and monthly family income (ρ=0.361). The main barrier that hold back from utilization of these services was lack of knowledge and ignorance followed by poverty.Conclusion: This study reveals low utilization of pregnancy related care among the tea garden workers. Effective steps should be taken to encourage the proper utilization of pregnancy related care in this community.JOPSOM 2019; 38(2): 38-45